2016
DOI: 10.1111/ggi.12731
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic or independent impacts of low frequency of going outside the home and social isolation on functional decline: A 4‐year prospective study of urban Japanese older adults

Abstract: Social isolation regardless of going outside the home every day for men and going outside the home less than every day regardless of being not socially isolated for women might predict functional decline. Geriatr Gerontol Int 2017; 17: 500-508.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 20 publications
0
41
3
Order By: Relevance
“…The study protocol was approved by the Institutional Review Board of the Tokyo Metropolitan Institute of Gerontology (TMIG). The sampling method of the study has been provided elsewhere [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol was approved by the Institutional Review Board of the Tokyo Metropolitan Institute of Gerontology (TMIG). The sampling method of the study has been provided elsewhere [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…We defined the terms "isolation" and "homeboundness" based on the definitions provided by Fujiwara et al 15 . This definition uses questions on in-person social contact ("How often do you see or go out with friends, neighbors, and family members who do not live at your dwelling?")…”
Section: Evaluation Of Isolation and Homeboundnessmentioning
confidence: 99%
“…12 Although operative definitions of these terms vary from study to study, the reported incidences of social isolation and homeboundness in the elderly are 7-17% 13 and 5.6%, 14 respectively. Fujiwara et al 15 defined social isolation as having less than one interaction with others per week, regardless of whether the interaction is in person or not, and homeboundness as leaving the house less than once a day. They surveyed these parameters in community-dwelling elderly and found that the incidences of social isolation and homeboundness were 34.4% and 22.9% for men and 15.6% and 32.9% for women, respectively, and that these parameters were associated with decline in high-level functional capacity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations